Phosphine Organocatalysis in the Synthesis of Natural Products and Bioactive Compounds. Issue 5 (12th October 2012) - Gomez, Catherine; Betzer, Jean‐François; Voituriez, Arnaud; Marinetti, Angela
Abstract During the last few years, synthetic methods based on phosphine organocatalysis have experienced extremely fast developments. This short overview is intended to demonstrate that these methods can afford suitable tools for the constitution of either focused or diversity‐oriented‐synthesis (DOS) inspired libraries of small molecules for biological screening. It also reports selected examples where these organocatalytic methods have been used conveniently as key steps in the formal or total synthesis of complex natural products. Especially, synthetic applications of the inter‐ and intramolecular cyclizations of unsaturated substrates have been considered in this review.